China and India’s Comparative Response to the 2017 Rohingya Crisis in Bangladesh - Maisaa Mehzabin; MD. Kawser Rahim Shuvo (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
The simultaneous rise of China and India has been creating significant re-orientation in the contemporary international system. Both the countries are trying to climb up in the global power hierarchy but for the first instance, they are competing with each other for the Pan-Asian leadership. As a result, their neighboring countries like Bangladesh and Myanmar are becoming hot spots for geostrategic power play between the two Asian powers. The Sino-Indian geostrategic competition intensified after 25 August 2017 when the military crackdown happened at the Rakhine state on Rohingya people. This paper illustrates the nature and dimensions of the response from New Delhi and Beijing on the 2017 Rohingya Refugee crisis. This paper adopted a qualitative method and data was analyzed based on secondary data. The findings argue that there was a qualitative difference between the responses from India and China in this crisis. India claimed to remain neutral in the crisis and provided limited humanitarian and economic assistance to Bangladesh and Myanmar. This paper also reviews why China and India back Myanmar and the international response to this crisis. Finally, this paper concludes with Bangladesh’s challenges from the Sino-Indian geostrategic interests in the Rakhine state.